Depletion of Hypocretin/Orexin Neurons Increases Cell Proliferation in the Adult Subventricular Zone - Arias-Carrion, Oscar; Ortega-Robles, Emmanuel; de Celis-Alonso, Benito; Palasz, Artur; Mendez-Rojas, Miguel A.; Salas-Pacheco, Jose; Murillo-Rodriguez, Eric (CNS & Neurological Disorders - Drug Targets, 2018)
Background & Objective: Adult neurogenesis, a specific form of brain plasticity in mammals that occurs in the subventricular zone, is subject to complex regulation. Hypocretin/orexin neurons are implicated in the regulation of sleep and arousal states, among other functions. Here we report for the first time the presence of orexinergic projections within the adult rat subventricular zone. Post-mortem retrograde tracing combined with immunofluorescence indicated orexinergic projections toward the subventricular zone. To establish the relationship between the depletion of orexin neurons and the number of proliferating cells in the subventricular zone, we labeled mitotic cells. Histological analysis revealed proliferating cells to be in close contact with orexinergic fibers. Neurotoxinlesioning of orexin neurons in the lateral hypothalamus significantly activated precursor cell proliferation in the subventricular zone. Furthermore, cell proliferation in both normal and lesioned animals failed to reveal newly born orexin neurons in the lateral hypothalamus. Conclusion: Based on these findings, we suggest that the adult subventricular zone is affected by orexinergic signaling, the functional implication of which must be further elucidated.
Keywords: hypothalamic area